Distribution, preparedness and management of Ukrainian adult refugees on dialysis - an international survey by the Renal Disaster Relief Task Force of the European Renal Association - TUĞLULAR, ZÜBEYDE SERHAN (My University, 2023)
Background: Due to the Russian-Ukrainian war, some of the about 10 000 adults requiring dialysis in Ukraine fled their country to continue dialysis abroad. To better understand the needs of conflict-affected dialysis patients, the Renal Disaster Relief Task Force of the European Renal Association conducted a survey on distribution, preparedness and management of adults requiring dialysis who were displaced due to the war. Methods: A cross-sectional online survey was sent via National Nephrology Societies across Europe and disseminated to their dialysis centers. Fresenius Medical Care shared a set of aggregated data. Results: Data were received on 602 patients dialyzed in 24 countries. Most patients were dialyzed in Poland (45.0%), followed by Slovakia (18.1%), Czech Republic (7.8%) and Romania (6.3%). The interval between last dialysis and the first in the reporting center was 3.1 ± 1.6 days, but was ≥4 days in 28.1% of patients. Mean age was 48.1 ± 13.4 years, 43.5% were females. Medical records were carried by 63.9% of patients, 63.3% carried a list of medications, 60.4% carried the medications themselves and 44.0% carried their dialysis prescription, with 26.1% carrying all of these items and 16.1% carrying none. Upon presentation outside Ukraine, 33.9% of patients needed hospitalization. Dialysis therapy was not continued in the reporting center by 28.2% of patients until the end of the observation period. Conclusions: We received information about approximately 6% of Ukrainian dialysis patients, who had fled their country by the end of August 2022. A substantial proportion were temporarily underdialyzed, carried incomplete medical information and needed hospitalization. The results of our survey may help to inform policies and targeted interventions to respond to the special needs of this vulnerable population during wars and other disasters in the future.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Nefroloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Nephrology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ÜROLOJİ VE NEFROLOJİ; TRANSPLANTASYON; Clinical Medicine (MED); CLINICAL MEDICINE; UROLOGY & NEPHROLOGY; TRANSPLANTATION; Transplantasyon; Transplantation; conflicts; dialysis; disasters; refugees; wars